Assessing Aspects of Professional Collaboration in Schools: Beliefs Versus Practices - Leonard, Pauline; Leonard, Lawrence (Alberta Journal of Educational Research, 2001)
Much has been written about the potential of professional collaboration to advance the purposes of schooling, yet much remains to be learned about the extent to which teachers themselves value such practices. This article reports the findings of a survey questionnaire completed by 565 randomly selected classroom teachers in 96 school districts in Western Canada. Using selected dimensions of organizational culture as the basis of inquiry, the researchers investigated teachers' perceptions regarding collaborative activities, diversity in education, the usage of teacher time, and the nature of professional relationships. Comparisons of teachers' espoused beliefs with impressions of actual conditions and circumstances in their schools reaffirmed some popular conceptions about the potential for high-involvement schools to realize educational goals. However, they also showed that teachers continue to wrestle with conflictual circumstances arising from the confluence of their own aspirations, the expectations of others, and the continuing limitations that severely curtail the realization of normative learning communities.